Controlling effluent suspended solids in the aerobic granular sludge process. (15th December 2018) - van Dijk, Edward J.H.; Pronk, Mario; van Loosdrecht, Mark C.M.
Abstract: The main processes contributing to elevated effluent suspended solids in the full-scale aerobic granular sludge process were studied. The two processes found to be most important were (1) rising of sludge due to degasification of nitrogen gas (produced by denitrification) and (2) wash-out of particles that intrinsically do not settle such as certain fats and foams. A mathematical model was made to describe the process of degasification of nitrogen gas during the feeding phase in an AGS reactor. The process of rising sludge due to degasification could be limited by stripping out the nitrogen gas before starting the settling phase in the process cycle. The wash-out of scum particles could be reduced by introducing a vertical scum baffle in front of the effluent weir, similar to weirs in traditional clarifiers. A full-scale Nereda ® reactor in the municipality of Utrecht, The Netherlands, was operated with a nitrogen stripping phase and scum baffles for 9 months at an average biomass concentration of 10 g L − 1 and an average granulation grade of 84%. In this period the influent suspended solids concentration was 230 ± 118 mg L − 1 and the concentration of effluent suspended solids was 7.8 ± 3.8 mg L − 1 . Graphical abstract: Highlights: Mechanisms for production of effluent suspended solids in AGS reactors unravelled. Stripping of nitrogen gas prevents rising sludge. Vertical baffle prevents washout of fat-like particles and scum. Mathematical model of rising sludge describes stripping of nitrogen gas.